Research of production times and cutting of the spur gears by end mill in CNC milling machine - Ozel, Cihan (Springer London Ltd, 2011)
In the current study, differently from the conventional manufacturing methods, cutting of spur gear by the end mill in the computer numerically controlled (CNC) vertical milling machine was purposed. For this aim, two different approaches, radial and axial cutting methods, were introduced. However, the cutting process is performed by use of only the radial cutting method. Parametric equations of tool paths for cutting the spur gear were derived. Regarding those equations, by using the macro-program of the Dyna 2009 Myte type CNC milling machine, a CAM program is developed. By varying the parameters in the tool paths such as module, number of teeth, face width of the spur gear, cutting depth, and cutting angle, spur gear was cut and the production time was obtained. Furthermore, the dimensions of new manufactured spur gear were measured by gear tooth vernies. The dimensions were also calculated by using mathematical expressions and it was concluded that the measured values are well agreeable with the calculated values. It was observed that the production time increases with increasing the module value or number of teeth and decreasing the cutting angle or the cutting depth.
Keywords: Spur gear cutting; End mill; CNC milling machine; Production times